EFFICACY OF HERBAL HEAT INDUCERS AND MINERAL SUPPLEMENTATIONS FOR INDUCING FERTILITY IN POST PARTUM ANOESTRUS DECCANI SHEEP - PATIL, A D; RAGHUWANSHI, D S; KUMBHAR, U B; MAINl, SHIV (The Indian Journal of Animal Reproduction, 2023)
The study was conducted to evaluate the efficacy of herbal heat inducer and mineral supplementationin 40 postpartum anoestrus Deccani Sheep. The experimental ewes were selected from Sheep unit,Veterinary College and Private Sheep units located around Udgir (MS). The animals were divided intofour groups. Each group consisting ten sheep. Group I were administered orally with Capsule Janova@2 Cap. daily for three days, repeat the dose after 1 O days if no estrus is observed. Group II were treatedwith Exapar liquid (@20 ml daily/ sheep for 5 day)+ Tab. Mintrus (@one Tab./daily,for 20 days)+ Cap.Janova (@2 cap. for 3 days). Group Ill were administered withAV/UTU17 (@20 ml daily/ sheep for 5day)+ Tab. Mintrus (@one Tab./dailyfor 20 days)+ Cap. Janova (@2 cap. for 3 days). Group IV waskept as untreated control. In group I, 80.00 per cent of the sheep showed oestrus within 127 .25 ± 4.26hrs. and conception rate was 75.00 % with 1.67 services per conception. In Group II 90.00 per centshowed oestrus within 86.00 ± 4.53 hrs and conception rate was found to be 66.67 % with 1.5 servicesper conception. In Group 11190.00 per cent showed oestrus within 38.25 ± 8.58 hrs and conception ratewas observed 88.89 % with 1.25 services per conception. In control group IV 30.00 per cent showedoestrus within 165.87 ± 6. 77 hrs and 33.33 % conceived with 1.5 services per conceptions. Induction offertile postpartum oestrus in Deccani sheep was found to be effective with AV/UTU17 (herbal uterinecleanser) + Mintrus + Janova administration followed by post partum anoestrus could be treatedsuccessfully with Exapar + Mintrus + Janova combination therapy.
Keywords: Herbal heat inducer; Mineral supplementations; Post partum anoestrus; Deccani Sheep